Authors (The Biblical archaeology review, 2021)
Roy Albag ("Reconstructing the Church of the Glorious Martyr" sidebar) is an architect specializing in 3D archaeological research. He is currently working on the Tel Moẓa temple, the topic of his doctoral research at Osnabrück University, Germany.